A study of the Arundel Society 1848-1897 - Ledger, T (1978)
This thesis gives, for the first time, a clear exposition of the activities of the Arundel Society (1848-1897). Founded to 'collect diligently and with discrimination the highest and best examples of Art and to bring them before hundreds of English minds' the presence of Aubrey Bezzi, Lord Lindsay, Edmund Oldfield, Samuel Rogers and John Ruskin on the Society's first council meant that the initial publication of engravings after two early Italian artists, Fra Angelico and Giotto, was unsurprising. After 1856, under the guidance of Henry Layard, the archaeologist and politician, the Society became even more firmly committed to copying and publishing frescoes of the early Renaissance. The council's aim in recording and publishing these endangered works of art was to educate the taste of the public and inspire artists to embark on programmes of mural decoration. The water-colours executed for the Society are discussed with particular reference to the reactions of the council, and of members and the press to the problem of their verisimilitude. About two-thirds of these copies were published as chromolithographs and the gains and liabilities of this initially very popular method of reproduction are examined. Other methods employed by the Society to publish fac-similies of classical and medieval ivories and reduced copies of the Elgin marbles are also discussed with general reference to Victorian attitudes towards reproductions. The penultimate chapter attempts to relate the prints and monographs published by the Society to the art historical scholarship of the period. It is shown that the council's publication of decorative quattrocento, provincial cinquecento and early Flemish and German artists was influenced by Henry Layard's preferences. His monographs for the Society are discussed and compared with the more scholarly, if diverse, contributions made by, among others, G. W. Kitchin, John Ruskin, George Scharf and Ralph Wornum. In the final chapter it is argued that the Society's loyalty to the tastes of the mid-century and to the process of chromolithography led to its dissolution.